Sahara occidental : divergences profondes autour d’un mode de règlement - Khadija Mohsen-Finan (L’Année du Maghreb)
The Western Sahara conflict is entering its thirty-fifth year without any sign that one or another of the parties is gaining the upper hand. The players have adopted an all-or-nothing posture regarding the outcome of the conflict : Morocco preaches Saharan autonomy within the kingdom, while the Algeriens and Sahrawis of the Polisario Front hold out for sovereign autonomy. In the absence of a clear victory for one or the other of the protagonists, the political solution will require a compromise reflecting the balance of power. Anxious to pacify and stabilize a region that could provide refuge for Al-Qaeda in the Islamic Maghreb, Washington, Paris and Madrid support the United Nation’s special envoy for the Western Sahara in seeking a compromise solution to accommodate all the players. The parties to such a compromise must however, take into account the overall Sahrawi population and geostrategic balance in the region.